When you do "substitution", you replace part of an equation with something that is of equal value. The equal sign is your friend here, because it tells you that what is on one side is equal in value to what is on the other side.

The first equation tells us that -3s may be substituted for r. The second equation gives an opportunity to find the value of s after that substitution is made

r = -3s

(r) + 4s = 10

(-3s) + 4s = 10 (after substituting -3s for r)

s = 10 (collect terms)

r = -3(s)

r = -3(10) (substitute for s)

r = -30

The solution is (r, s) = (-30, 10).

The first equation tells us that -3s may be substituted for r. The second equation gives an opportunity to find the value of s after that substitution is made

r = -3s

(r) + 4s = 10

(-3s) + 4s = 10 (after substituting -3s for r)

s = 10 (collect terms)

r = -3(s)

r = -3(10) (substitute for s)

r = -30

The solution is (r, s) = (-30, 10).